Novel food sources for Quiscalus mexicanus and Cyanocorax sanblasianus in Chamela, Jalisco coast, Mexico. - Gurrola Hidalgo, Marco A.; Sánchez-Hernández, Cornelio; Romero Almaraz, María de Lourdes (Instituto de Ecología, A.C., 2009)
Information over the feeding habits of neotropical birds have been relatively few documented, this is the first report in México over the depredation of the mole crabs (Emerita spp.) by the Great-tailed Grackle (Quiscalus mexicanus) and for Ruddy-ground Dove (Columbina talpacoti) by San Blas Jay (Cyanocorax sanblasianus), in the coast of Chamela, Jalisco, México.